All-arthroscopic AMIC® (AT-AMIC) in the treatment of osteochondral talar lesions - Baumfeld, Tiago Soares; Baumfeld, Daniel Soares; Prado, Marcelo Pires; Nery, Caio Augusto de Souza (Scientific Journal of the Foot & Ankle, 2018)
Objective: The objective of this study was to report the postoperative clinical outcomes of patients undergoing the all-arthroscopic AMIC® technique (AT-AMIC®) combined with autologous bone graft placement as necessary. Methods: This was a case series of 17 consecutive patients who underwent AT-AMIC® between January 2016 and April 2017. Nine men and eight women between 15 and 67 years of age were diagnosed with an osteochondral talar lesion (OTL) and underwent surgery only after failure of conservative treatment of at least 3 months. Patients answered the AOFAS scale before surgery and at the final follow-up session, which ranged from 8 to 20 months. Results: The mean size of the OTLs was 1.16cm2, and “Raikin-4” was the most common site of lesions (71%). Calcaneal osteotomy was the most commonly associated procedure (18%). The mean follow-up period was 12.3 months. The mean AOFAS score before surgery was 46.4 points, rising to 89.5 points at the last follow-up, and this difference was statistically significant (p<0.001). No complications were observed in any of the treated patients. Conclusion: AT-AMIC® is a reliable and reproducible treatment method for OTLs and achieves high postoperative clinical scores with very low complication rates. Level of Evidence IV; Therapeutic Studies; Case Series.